Heat exchanger design guide : a practical guide for planning, selecting and designing of shell and tube exchangers /: a practical guide for planning, selecting and designing of shell and tube exchangers. (2015) - Nitsche, Manfred; Gbadamosi, Raji Olayiwola
No abstract available